Pelatihan MIT App Inventor sebagai Upaya Meningkatkan Kemampuan Berpikir Logis Siswa SMAN 4 Parepare - Maharani, Putri Ayu; Gunadin, Indar Chaerah; Intizhami, Naili Suri; Nuranti, Eka Qadri; Rafrin, Mardhiyyah; Agus, Muh.; Iskandar, M. Fauzan; Yunus, Sitti Rahma; Al-Fauzi S., Muhammad Faruq; Tunru, Muh. Abubakar (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to improve the logical thinking abilities of SMAN 4 Parepare students by teaching the application of mathematical logic in compiling computer instructions based on MIT App Inventor. The method for implementing this service was problem-based learning training by taking the example of the traditional game of rock-paper-scissors as a learning case. Next, create a rock-paper-scissors game program using MIT App Inventor as a student learning experience in applying mathematical logic concepts. The evaluation instrument employed was a questionnaire to collect pre-test and post-test results, which were then analyzed using descriptive statistics and paired sample t-tests. The results of this service showed an increase in the average participant score on the post-test results, where the average pre-test score was 7.24 out of 15, while the average post-test score was 9.17 out of 15.